Optimalisasi Lahan Kosong Sebagai Strategi Penurunan Penyakit Degeneratif Pada Kelompok Lansia Sekar Gadung Pasuruan - Nur Wahidah, Vyas; Falasifah, Nihlatul (Journal of Community Development and Disaster Management, 2024)
Kalipang village is in Grati sub-district, Pasuruan regency which has an area of ​​287,550 hectares. Kalipang village has a relatively large population of various age levels. In Krikilan hamlet, the number of elderly people reaches 62 people. From the results of health checks carried out, it shows that there are many degenerative diseases suffered by the elderly. Degenerative diseases, including high blood pressure, gout, cholesterol. This degenerative disease occurs due to an unhealthy lifestyle and other factors carried out at a young age. The method used is interviews and observation. The results show that many elderly people suffer from degenerative diseases in the Sekar Gadung elderly group, so they use empty land to plant family medicinal plants (TOGA). The benefits of TOGA are quite numerous for health. Reducing the impact of degenerative diseases in the elderly is a practical and natural way.